Temporary fixing composition
Patent Information
- Application Number
- JP2024509795
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-01-25
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2043-01-25
AI Technical Summary
【0028】 本発明によれば、仮固定用途において優れた耐熱性を呈し、かつテープ剥離時のテープの割れを抑制できる新規な仮固定用組成物が得られる。
Smart Images

Figure 0007638439000001 
Figure 0007638439000002 
Figure 0007638439000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for use in temporary fixation. [Background technology]
[0002] In the manufacture of electronic devices, inorganic materials such as silicon are used as substrates. Wafer-type substrates with a thickness of about several hundred μm are often used, which are obtained by processing the surface of the substrate, such as forming an insulating film, forming a circuit, and thinning the substrate by grinding. However, since many substrates are made of brittle and easily cracked materials, measures to prevent damage are necessary, especially when thinning the substrate by grinding. A conventional method for preventing this is to apply a temporary protective tape to the surface opposite to the surface to be ground (also called the back surface), which can be peeled off after the processing process is completed. This tape uses an organic resin film as the base material, and while it is flexible, it is insufficient in strength and heat resistance, making it unsuitable for use in high-temperature processes.
[0003] In response to this, a system has been proposed in which an electronic device substrate is bonded to a support such as silicon or glass via an adhesive, thereby providing sufficient durability to withstand the conditions of the back grinding and back electrode formation processes. In this case, the adhesive layer used to bond the substrate to the support is important. This must be able to bond the substrate to the support without any gaps, and must be durable enough to withstand subsequent processes. Finally, it must be possible to easily peel off the thinned wafer from the support, i.e., to temporarily fix it.
[0004] The processing of such wafers mainly involves a spin coating step, a vacuum bonding and light curing step, thinning by grinding and polishing, a high-temperature treatment step, a laser peeling step, and a temporary fixing agent removal step.
[0005] In the spin coating process, in order to form a uniform film of the temporary fixative on the wafer, it is required that the temporary fixative has an appropriate viscosity and is a Newtonian fluid (or has a shear viscosity that is independent of the shear rate).
[0006] In the vacuum bonding / UV curing process, the temporary fixative must be able to cure in a short time on a support such as glass by exposure to ultraviolet (UV) light, and must generate little outgassing (low outgassing properties).
[0007] In the thinning process by grinding and polishing, in order to avoid damage caused by the load of the grinding machine being applied locally to the substrate, the temporary fixative must have an appropriate hardness to distribute the load in the in-plane direction while preventing localized sinking of the substrate and maintaining flatness. In addition, adhesive strength with the support, an appropriate elastic modulus to protect the edges, and chemical resistance are also required.
[0008] In the high-temperature treatment step, the temporary fixing agent is required to have heat resistance capable of withstanding high-temperature treatment in a vacuum for a long period of time (for example, at 300° C. or higher for one hour or more).
[0009] In the laser peeling process, the temporary fixative is required to be able to be peeled off quickly by a laser such as a UV laser.
[0010] In the removal step, in addition to easy peelability so that the substrate can be easily peeled off from the support, the adhesive is required to have cohesive properties so that no adhesive residue remains on the substrate after peeling, and easy cleanability.
[0011] In view of this background, for example, Patent Document 1 discloses a temporary fixing composition containing (A-1) a monofunctional (meth)acrylate whose side chain is an alkyl group having 18 or more carbon atoms and whose homopolymer has a Tg of -100°C to 60°C, (A-2) a polyfunctional (meth)acrylate, (B) a polyisobutene homopolymer and / or a polyisobutene copolymer, and (C) a photoradical polymerization initiator, and claims that the composition has excellent heat resistance, low outgassing properties, and peelability. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] International Publication No. 2021 / 235406 Summary of the Invention [Problem to be solved by the invention]
[0013] As the demand for higher integration and smaller electronic devices increases, the substrate is becoming thinner, and substrates with thicknesses of 70 μm and 50 μm are now in practical use. With such thin substrates, if the tape on the substrate breaks when the tape is peeled off, the impact can damage the electronic device. There is a need for developments beyond the conventional technology to further improve tape peelability while still satisfying the above-mentioned demands, especially heat resistance. [Means for solving the problem]
[0014] That is, the present invention can provide the following aspects.
[0015] Aspect 1. A temporary fixing composition comprising the following (A) and (B), the composition having a storage modulus of elasticity of a cured product at 23° C. of 0.66 GPa or less: (A) Bifunctional (meth)acrylate having a cyclic skeleton (B) Photoradical polymerization initiator The cured product was sandwiched between PET films and spread to a thickness of 50 μm. Then, UV-LED (center wavelength 405 nm, illuminance 100 mW / cm 2 ) with an accumulated light dose of 5000mJ / cm 2 The composition was cured under the following conditions.
[0016] Aspect 2. The component (A) is (A-1) Aromatic bifunctional (meth)acrylate, and (A-2) Alicyclic bifunctional (meth)acrylate 2. The temporary fixing composition according to claim 1, comprising:
[0017] Aspect 3. The temporary fixing composition according to aspect 1 or 2, further comprising the following (C): (C) Acyclic aliphatic bifunctional (meth)acrylate
[0018] Aspect 4. The temporary fixing composition according to aspect 3, wherein the component (C) includes an oligomer and / or a polymer.
[0019] Aspect 5. The temporary fixing composition according to aspect 3 or 4, wherein the amount of the component (A) is 50% or more in the mass ratio of the component (A) to the component (C).
[0020] Aspect 6. The temporary fixing composition according to any one of Aspects 1 to 5, further comprising the following (D): (D) UV absorber
[0021] Aspect 7. The temporary fixing composition according to any one of Aspects 1 to 6, further comprising the following (E): (E) Monofunctional (meth)acrylate
[0022] Aspect 8. The temporary fixing composition according to embodiment 7, wherein the component (E) is contained in an amount of more than 0% and 50% or less in terms of the mass ratio of the component (A) to the component (E).
[0023] Aspect 9. The temporary fixing composition according to any one of Aspects 1 to 6, which does not contain a monofunctional (meth)acrylate.
[0024] Aspect 10. The temporary fixing composition according to any one of Aspects 1 to 9, further comprising the following (F): (F) Trifunctional or higher polyfunctional (meth)acrylate
[0025] Aspect 11. A temporary fixing composition according to embodiment 10, wherein the component (F) is contained in an amount of more than 0% and 50% or less in terms of a mass ratio of the component (A) to the component (F).
[0026] Aspect 12. A cured product of the temporary fixing composition according to any one of aspects 1 to 11.
[0027] Aspect 13. 13. The cured product according to embodiment 12, which has a 2% mass loss temperature of 300° C. or higher under a nitrogen atmosphere. Effect of the Invention
[0028] According to the present invention, a novel temporary fixing composition is obtained which exhibits excellent heat resistance in temporary fixing applications and can suppress cracking of the tape when the tape is peeled off. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] In this specification, unless otherwise specified, the numerical range includes the upper and lower limits. In this specification, a monofunctional (meth)acrylate refers to a compound having one (meth)acryloyl group in one molecule. A multifunctional (meth)acrylate refers to a compound having two or more (meth)acryloyl groups in one molecule. An n-functional (meth)acrylate refers to a compound having n (meth)acryloyl groups in one molecule. The polymerizable functional group in the multifunctional (meth)acrylate may have only an acryloyl group, may have only a methacryloyl group, or may have both an acryloyl group and a methacryloyl group.
[0030] In an embodiment of the present invention, a temporary fixing composition (also referred to as a "temporary fixing agent") can be provided, which contains (A) a bifunctional (meth)acrylate having a cyclic skeleton and (B) a photoradical polymerization initiator, and has a storage modulus of 0.66 GPa or less at 23°C. In this specification, the cured product used for measuring the storage modulus is prepared by sandwiching the temporary fixing composition between PET films, spreading it to a thickness of 50 μm, and irradiating it with a UV-LED (center wavelength 405 nm, illuminance 100 mW / cm). 2 ) with an accumulated light dose of 5000mJ / cm 2 It is assumed that the composition is cured under the above conditions.
[0031] The bifunctional (meth)acrylate having a cyclic skeleton, which is the component (A) contained in the composition, plays a role of forming a rigid skeleton in the composition, and can provide an effect of appropriately improving the viscosity. Examples of the bifunctional (meth)acrylate include (A-1) an aromatic bifunctional (meth)acrylate and (A-2) an alicyclic bifunctional (meth)acrylate. In a preferred embodiment, the component (A) may contain either the component (A-1) or the component (A-2), or may contain both the component (A-1) and the component (A-2). The component (A) is preferably a monomer.
[0032] The aromatic bifunctional (meth)acrylate component (A-1) is preferred because it can generally form a more rigid skeleton. More preferably, the component (A-1) may have a condensed ring skeleton to further increase the rigidity.
[0033] Examples of the (A-1) component include 9,9-bis[4-(2-hydroxyC1-C 20 Alkoxy)phenyl]fluoren-di(meth)acrylate, C1-C 20 Alkoxylated bisphenol A di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C1-C 20 Examples of the di(meth)acrylate include 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, and structural isomers thereof. Preferably, the di(meth)acrylate may have a condensed ring skeleton, such as a skeleton of fluorene, indene, indecene, anthracene, azulene, or triphenylene. One or a combination of two or more of these may be used as the component (A-1).
[0034] The alicyclic bifunctional (meth)acrylate, which is the component (A-2), is generally less rigid than the above-mentioned component (A-1), but is generally a component that can provide a more rigid skeleton than a non-cyclic molecule (such as a non-cyclic bifunctional (meth)acrylate). In a preferred embodiment, the combination of the component (A-2) with the component (A-1) makes it possible to form a crosslinked structure that provides preferred physical properties for the temporary fixing agent. Preferably, the component (A-2) may have a condensed ring skeleton to further increase the rigidity. Preferably, the component (A) may contain the component (A-2) having a condensed ring skeleton together with the component (A-1) having a condensed ring skeleton. In an embodiment, the number of rings (including condensed rings) possessed by the component (A-1) or the component (A-2), or both, may be two or more, and preferably two or more and five or less.
[0035] Examples of the (A-2) component include C1 to C 20 Alkoxylated hydrogenated bisphenol A di(meth)acrylate, 1,3-di(meth)acryloyloxyadamantane, tricyclo C 10 ~C 20 Alkanedimethanol di(meth)acrylate (e.g. tricyclodecane dimethanol di(meth)acrylate, etc.), dicyclo C5-C 20 Di(meth)acrylates, or structural isomers thereof. Among the alicyclic bifunctional (meth)acrylates, alicyclic bifunctional (meth)acrylates having an alicyclic skeleton with 5 or more carbon atoms are more preferred. As the alicyclic bifunctional (meth)acrylate having an alicyclic skeleton with 5 or more carbon atoms, one or more selected from tricyclodecane dimethanol di(meth)acrylate and 1,3-di(meth)acryloyloxyadamantane are preferred.
[0036] In an embodiment in which the component (A) contains both the component (A-1) and the component (A-2), the mass ratio of the component (A-1) to the component (A-2) may be preferably in the range of 1:1 to 4:1, and more preferably in the range of 2:1 to 4:1.
[0037] The photoradical polymerization initiator, which is the component (B) contained in the present composition, is a substance capable of initiating radical polymerization of the component (A) (and other monomers contained as necessary) upon irradiation with light, and is, for example, a compound whose molecules are cleaved and split into two or more radicals upon irradiation with ultraviolet light or visible light (for example, wavelengths of 350 to 700 nm, preferably 365 to 500 nm, and more preferably 385 to 450 nm). Examples of photoradical polymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(η 5 -2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)-butan-1-one, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime). The (B) component may contain one or more of these in combination.
[0038] Preferably, the (B) component may contain an acylphosphine oxide-based compound. Examples of preferred acylphosphine oxide-based compounds include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide. As the photoradical polymerization initiator, it is preferable that it is highly sensitive, has excellent deep curing properties due to its photofading properties, and has an absorption wavelength range for generating radicals that extends to a relatively long wavelength range. In the above-mentioned preferred compounds, the absorption wavelength range is in the range up to a wavelength of about 440 nm, which is significantly different from the absorption wavelength range of the UV absorber used in the UV laser peeling process described later. In other words, the degree of UV curing inhibition by the UV absorber is small, and radical polymerization can be initiated with light of a longer wavelength. Therefore, even in the presence of a UV absorber, the effect of initiating radical polymerization and curing efficiently at a relatively high speed can be obtained.
[0039] In a preferred embodiment, the photoradical polymerization initiator can be selected based on absorbance. Specifically, the photoradical polymerization initiator can be selected from one or more compounds that satisfy one or more of the following conditions when dissolved at a concentration of 0.1 mass % in a solvent (e.g., acetonitrile, toluene, etc.) that does not have a maximum absorption in the wavelength region of 300 to 500 nm: absorbance of 0.5 or more at a wavelength of 365 nm, absorbance of 0.5 or more at a wavelength of 385 nm, and absorbance of 0.5 or more at a wavelength of 405 nm. Examples of compounds that satisfy such conditions include 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime), which has an absorbance of 0.5 or more at a wavelength of 365 nm when dissolved in acetonitrile as a solvent at a concentration of 0.1% by mass; 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, which has an absorbance of 0.5 or more at wavelengths of 365 nm and 385 nm; and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide, which have an absorbance of 0.5 or more at wavelengths of 365 nm, 385 nm, and 405 nm.
[0040] In addition, from the viewpoint of achieving both the curing property by the photoradical polymerization initiator and the UV laser peeling property, bis(η 5 -2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium can also be used as a photoradical polymerization initiator.
[0041] As the (B) photoradical polymerization initiator, one or more selected from acylphosphine oxide compounds, titanocene compounds, and α-aminoalkylphenone compounds are preferred in terms of reaction speed, heat resistance after curing, low outgassing, and absorption characteristics in a region different from the wavelength of the UV laser used in the UV laser peeling described later and the absorption wavelength region of the UV absorber used in the UV laser peeling. In addition, among the temporary fixing compositions having the structure described later, an oxime ester compound can also be selected as a photoradical polymerization initiator for a resin composition for temporary fixing purposes for preventing damage from bonding of a substrate to be processed to a support substrate to a heating step, which is not a layer for responding to the UV laser peeling process.
[0042] Examples of the acylphosphine oxide compound include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, etc. Among these, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is particularly preferred.
[0043] Titanocene compounds include bis(η 5 -2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium.
[0044] Examples of the α-aminoalkylphenone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)-butan-1-one, and the like.
[0045] Examples of oxime ester compounds include 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime), etc. Among these, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime) is preferred.
[0046] The amount of the photoradical polymerization initiator (B) used is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 1 part by mass, per 100 parts by mass of the component (A) in terms of reaction rate, heat resistance after curing, and low outgassing. When the amount of the component (B) is 0.01 part by mass or more, sufficient curability is obtained, and when it is 5 parts by mass or less, the effect of low outgassing and heat resistance being less likely to be impaired is obtained.
[0047] The storage modulus E' of the cured product of the composition at 23°C is 0.66 GPa or less. If the storage modulus exceeds 0.66 GPa, the tape is likely to crack when a tape peeling step is performed in a temporary fixing application during the manufacture of an electronic device. The storage modulus can be measured by a known viscoelasticity measuring instrument, for example, by the method described in the Examples below. The storage modulus E' of the cured product of the composition at 23°C may be preferably 0.01 GPa or more and 0.66 GPa or less, 0.02 GPa or more and 0.66 GPa or less, or 0.05 GPa or more and 0.66 GPa or less. In a more preferred embodiment, the storage modulus E' of the cured product of the composition at 23°C may be 0.01 GPa or more and 0.60 GPa or less, or 0.01 GPa or more and 0.55 GPa or less.
[0048] From the viewpoint of ease of laser peeling, the storage modulus E' of the present composition is preferably 0.01 GPa or more at 23°C.
[0049] The present composition may contain an acyclic aliphatic bifunctional (meth)acrylate as component (C), which can impart flexibility to the crosslinked structure.
[0050] Examples of the (C) component include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 2,2-bis(4-(meth)acryloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxytetraethoxyphenyl)propane, isocyanuric acid ethylene oxide modified di(meth)acrylate, and caprolactone modified hydroxypivalic acid neopentyl glycol di(meth)acrylate.
[0051] Component (C) may comprise either a monomer, or an oligomer or polymer of said monomer, or any mixture thereof. In some embodiments, component (C) may not comprise a polymer.
[0052] When the present composition contains component (C), the amount of component (A) may be 50% by mass to 95% by mass, preferably 50% by mass to 90% by mass, more preferably 50% by mass to 85% by mass. In one embodiment, it is preferred that the mass ratio of component (A) to component (C) is 50% by mass to 95% by mass, and that component (C) does not contain a polymer.
[0053] The present composition may contain a UV absorber as component (D). The UV absorber refers to a compound whose molecules are cut and decomposed / vaporized by irradiation with ultraviolet light or a visible light laser, and the decomposition / vaporization occurs at the interface between the support substrate (or support) and the temporary fixing agent, causing a loss of the adhesive force between the temporary fixing agent and the support substrate (or support) that had been maintained up until just before the peeling step.
[0054] As the (D) UV absorber, one or more compounds selected from benzotriazole-based compounds and hydroxyphenyltriazine-based compounds are preferred in terms of the degree of overlap with the UV laser wavelength in the UV absorption wavelength region, the UV absorption characteristics at the same wavelength, low outgassing properties, and heat resistance.
[0055] As the benzotriazole-based compound, one or more selected from the group consisting of 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol], 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimido-methyl)-5-methylphenyl]benzotriazole are particularly preferred in terms of compatibility with the resin component, UV absorption characteristics, low outgassing properties, and heat resistance.
[0056] As the hydroxyphenyltriazine compound, one or more compounds selected from the group consisting of 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine, and 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine are particularly preferred in terms of compatibility with component (A), UV absorption characteristics, low outgassing properties, and heat resistance.
[0057] In a preferred embodiment for the UV laser peeling step, the most preferred UV absorber is one or more selected from the group consisting of 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine, or 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol]. These have excellent compatibility with component (A), high melting points, and relatively low vapor pressures under temperature conditions of about 300°C or less, so that the amount of use can be selected within a wide range, and can contribute to reducing outgassing from the cured temporary fixing composition under the temperature conditions.
[0058] As the UV absorber (D), it is most preferable to use an absorber selected based on the UV transmittance listed below. When component (D) has such a UV transmittance, it is possible to obtain the effect of appropriately controlling the curing and peeling of the composition.
[0059] When the UV absorbent is dissolved in a solvent that does not have a maximum absorption in the wavelength range of 290 to 410 nm at a concentration of 0.002% by mass, the transmittance at a wavelength of 355 nm and at a wavelength of 385 to 420 nm at an optical path length of 1 cm is preferably 50% or less, and more preferably 40% or less at a wavelength of 355 nm and 60% or more at a wavelength of 385 to 420 nm.
[0060] The most preferred (D) UV absorbers include, for example: 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (Tinuvin 900, manufactured by BASF; Adeka STAB LA-24, manufactured by Adeka Corporation; EVERSORB 76 / EVERSORB 234, manufactured by Everlight Chemical Co., Ltd.; molecular weight 447) has a transmittance of 20% or less at a wavelength of 355 nm and 60% or more at a wavelength of 385 to 420 nm when dissolved in toluene used as a solvent at a concentration of 0.002% by mass. 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (Tinuvin 928, manufactured by BASF; EVERSORB 89 / 89FD, manufactured by Everlight Chemical; molecular weight 442), which has a transmittance of 30% or less at a wavelength of 355 nm and 70% or more at a wavelength of 385 to 420 nm when dissolved in a concentration of 0.002% by mass in toluene as a solvent. 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (Tinuvin 405, manufactured by BASF, molecular weight 584), which has a transmittance of 40% or less at a wavelength of 355 nm and 90% or more at a wavelength of 385 to 420 nm when dissolved in tetrahydrofuran as a solvent at a concentration of 0.002% by mass at an optical path length of 1 cm. 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine (Tinuvin 460, molecular weight 630, manufactured by BASF), which is dissolved in a concentration of 0.002 mass % in tetrahydrofuran as a solvent and has a transmittance of 10% or less at a wavelength of 355 nm and 80% or more at a wavelength of 385 to 420 nm at an optical path length of 1 cm.
[0061] The UV transmittance of the cured product in this specification is a value obtained by reflectance measurement spectroscopy. Specifically, the transmittance is measured under the following conditions using a cured product film having a thickness of about 50 μm, which is prepared by sandwiching the film between PET resin sheets, and using a reflectance spectrometer (V-650 manufactured by JASCO Corporation).
[0062] Cell length: 10mm Photometry mode: T (Transmittance) Measurement range: 450-200nm Data capture interval: 1 nm UV / vis bandwidth: 2.0nm Response:medium Scanning speed: 40nm / min Light source switching: 340nm Light source: D2 / WI Filter switching: Step Correction: Baseline
[0063] The amount of the UV absorber (D) is preferably 0.01 to 5 parts by mass, more preferably 0.5 to 2.5 parts by mass, per 100 parts by mass of the (A) component. If it is 0.01 part by mass or more, a sufficient UV laser peeling speed can be obtained, and if it is 5 parts by mass or less, the effect of low outgassing properties and heat resistance being less likely to be impaired can be obtained.
[0064] The present composition may contain a monofunctional (meth)acrylate as component (E). As component (E), a monofunctional (meth)acrylate having a molecular weight of 550 or less is preferable, and a monofunctional alkyl (meth)acrylate having an alkyl group is more preferable.
[0065] The alkyl group is preferably one or more selected from linear alkyl groups, branched alkyl groups, and alicyclic alkyl groups, and more preferably one or more selected from linear alkyl groups and branched alkyl groups. From the viewpoint of improving compatibility with the (A) component, the (E) component preferably has a long-chain and branched or cyclic alkyl group, for example, a branched alkyl group having 18 to 40 carbon atoms, more preferably 18 to 32 carbon atoms, such as an isostearyl group, an isotetracosanyl group (e.g., 2-decyl-1-tetradecanyl group), an isotriacontanyl group (e.g., 2-tetradecyl-1-octadecanyl group), or a cycloalkyl group. By using such a long-chain, high-molecular-weight component having strong aliphatic hydrocarbon properties (more preferably by increasing the aliphatic hydrocarbon properties of the entire system), the low volatility, chemical resistance, and heat resistance required for the temporary fixing composition can be improved.
[0066] As the component (E), one or more selected from the group consisting of stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, 2-decyl-1-tetradecanyl (meth)acrylate, 2-dodecyl-1-hexadecanyl (meth)acrylate, and 2-tetradecyl-1-octadecanyl (meth)acrylate are preferred. As the component (E), the (meth)acrylate of the following formula 1 is preferred.
[0067] [ka] R 1 R is a hydrogen atom or a methyl group, and a hydrogen atom is more preferable. 2 is an alkyl group having a carbon number of preferably 18 to 32. One or more of these (meth)acrylates can be used.
[0068] R 2As the monofunctional alkyl (meth)acrylate in which R is an alkyl group having 18 to 32 carbon atoms, preferred are (meth)acrylates having a linear or branched alkyl group, such as stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicodecyl (meth)acrylate, behenyl (meth)acrylate, 2-decyl-1-tetradecanyl (meth)acrylate, and 2-tetradecyl-1-octadecanyl (meth)acrylate. From the viewpoint of preventing defects due to precipitation during production, 2 The number of carbon atoms is preferably 18 or more and 23 or less.
[0069] In an embodiment containing component (E), the amount of component (E) used is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less, per 100 parts by mass of the total of components (A) and (E). In another embodiment, it is preferable that the composition does not contain component (E), which can reduce the amount of outgassing and improve heat resistance. The amount of component (E) used may be more than 0% by mass.
[0070] The present composition may contain a trifunctional or higher (meth)acrylate as component (F). The molecular weight of component (F) is preferably 900 or less, more preferably 700 or less, most preferably 500 or less, and even more preferably 400 or less.
[0071] Examples of trifunctional (meth)acrylates that can be contained in the component (F) include isocyanuric acid ethylene oxide modified tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tris[(meth)acryloyloxyethyl]isocyanurate.
[0072] Examples of the tetrafunctional or higher (meth)acrylate contained in the component (F) include ditrimethylolpropane tetra(meth)acrylate, dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. Examples of the trifunctional or higher (meth)acrylate contained in the component (F) include (meth)acrylic copolymers having a (meth)acryloyl group in the side chain.
[0073] Among the (F) components, a (meth)acrylic copolymer having a (meth)acryloyl group in the side chain is preferred. An example of a (meth)acrylic copolymer having a (meth)acryloyl group in the side chain is "ART CURE RA-341" manufactured by Negami Chemical Industries Co., Ltd.
[0074] The amount of component (F) used is preferably 50 parts by mass or less, more preferably 1 to 40 parts by mass, and even more preferably 20 to 30 parts by mass, per 100 parts by mass of the total of components (A) and (F). When the amount of component (F) is 50 parts by mass or less, the composition after mixing is less likely to undergo phase separation and the heat resistance is less likely to decrease. The amount of component (F) used may be more than 0% by mass.
[0075] The weight average molecular weight in this specification is a value calculated as standard polystyrene by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is determined under the following conditions by using tetrahydrofuran as a solvent, using a GPC system (SC-8010 manufactured by Tosoh Corporation), and creating a calibration curve with commercially available standard polystyrene.
[0076] Flow rate: 1.0ml / min Set temperature: 40℃ Column configuration: 1 column of "TSK guardcolumn MP(xL)" 6.0mmID x 4.0cm manufactured by Tosoh Corporation, and 2 columns of "TSK-GELMULTIPOREHXL-M" 7.8mmID x 30.0cm (16,000 theoretical plates) manufactured by Tosoh Corporation, for a total of 3 columns (total of 32,000 theoretical plates) Sample injection volume: 100 μl (sample concentration 1 mg / ml) Liquid delivery pressure: 39kg / cm 2 Detector: RI detector (differential refractive index detector)
[0077] In some embodiments of the present invention, a cured product of the above-described composition can be provided. Such curing can be performed using a light source as described below. When the cured product is in the form of a cured film having a thickness of 50 μm, it is preferable that one or more of the following conditions are satisfied, and more preferably all of them are satisfied. The following conditions can be satisfied, for example, by using a UV absorber. The light transmittance of the cured film is 70% or more in the wavelength region of 395 nm or more of the wavelength of the light source used for curing. The light transmittance of the cured film in the wavelength region of 385 nm or more and less than 395 nm of the wavelength of the light source used for curing is 20% or more. The light transmittance of the cured film at the wavelength (355 nm) of the UV laser used for UV laser peeling must be 1% or less. By satisfying these conditions, it is possible to achieve both a sufficiently high curing speed and a UV laser peeling speed for practical use. Furthermore, in addition to achieving both a sufficiently high curing speed and a UV laser peeling speed, it is possible to reduce the rate of mass loss under heating conditions after curing (or reduce the amount of outgassing under high temperature vacuum). A temporary fixing agent with such properties can be suitably used in processes including high temperature vacuum processes such as ion implantation, annealing, and electrode formation by sputtering in the back surface process after thinning.
[0078] Spin coating is a method of applying the composition to the surface of a substrate by, for example, dropping a liquid composition onto the substrate and rotating the substrate at a predetermined rotation speed. By using spin coating, a high-quality coating film can be efficiently produced.
[0079] The composition can be used as a temporary fixing resin composition, a temporary fixing adhesive, a pressure-sensitive adhesive sheet, or a temporary fixing adhesive for electronic device production. In this specification, the temporary fixing composition, the temporary fixing resin composition, and the temporary fixing adhesive are sometimes collectively referred to as a temporary fixing agent.
[0080] When the composition is used to bond a substrate to be processed and an optically transparent support substrate (or support), the amount of energy in visible light or ultraviolet light (wavelength or central wavelength 365 to 405 nm) is 1 to 20,000 mJ / cm 2 It is preferable to irradiate so that the energy amount is 1 mJ / cm 2 Above this level, sufficient adhesion is obtained, and 20,000 mJ / cm 2 If the energy level is less than this, the productivity is excellent, decomposition products from the photoradical polymerization initiator are unlikely to be generated, and outgassing is suppressed. In terms of productivity, adhesion, low outgassing, and easy peeling, it is 1000 to 10000 mJ / cm 2 It is preferable that:
[0081] The substrate to be bonded by the composition is not particularly limited, but at least one of the substrates is preferably a transparent substrate that transmits light.The transparent substrate may be an inorganic substrate such as quartz, glass, quartz, calcium fluoride, magnesium fluoride, or an organic substrate such as plastic.Among these, an inorganic substrate is preferred because it is versatile and can provide a large effect.Among the inorganic substrates, one or more selected from glass and quartz are preferred.
[0082] The composition may be photocurable, and the cured product provided thereby has excellent heat resistance and peelability. In one embodiment, the cured product of the composition of the present invention has a small amount of outgas even when exposed to high temperatures, and is suitable for bonding, sealing, and coating various optical parts, optical devices, and electronic parts. The composition of the present invention is suitable for applications requiring a wide range of durability, such as solvent resistance, heat resistance, and adhesiveness, particularly for semiconductor manufacturing process applications.
[0083] The cured product of the composition can be used in processes in a wide range of temperatures from room temperature to high temperatures. The heating temperature during the process is preferably 350°C or less, more preferably 300°C or less, and most preferably 250°C or less. In a preferred embodiment, the temperature at which the heat mass loss rate of the cured product is 2% may be 250°C or more. The bonded product bonded with the composition has high shear adhesive strength and can withstand a thinning process, etc., and can be easily peeled off after a heating process such as insulating film formation. When used at high temperatures, the cured product of the composition can be used in high temperature processes, for example, preferably 200°C or more, more preferably 250°C or more.
[0084] In one embodiment, an adhesive is provided in which a substrate is bonded using the composition as an adhesive. The adhesive can be peeled off by applying an external force. For example, the adhesive can be peeled off by inserting a blade, sheet or wire into the bonded portion. Alternatively, the adhesive can be peeled off by irradiating the entire surface of the adhesive from the optically transparent substrate side with a UV laser or IR laser in a scanning manner.
[0085] <Method of manufacturing thin wafer> In one embodiment, a method for producing a thin wafer can also be provided. The method is characterized in that the above-mentioned temporary fixing composition or temporary fixing adhesive (hereinafter, sometimes simply referred to as adhesive or temporary fixing agent) is used as an adhesive layer between a wafer having a semiconductor circuit or the like and a support. The method for producing a thin wafer includes the following steps (a) to (e).
[0086] [Process (a)] Step (a) is a step in which, when bonding the circuit-forming surface of a wafer having a circuit-forming surface on its front side and a circuit-free surface on its back side to a support via an adhesive, the adhesive is applied onto the support or the wafer with the circuit by a spin coating method, and then the support or the wafer with the circuit is bonded to another support or wafer with the circuit under vacuum.
[0087] A wafer having a circuit-forming surface and a non-circuit-forming surface is a wafer in which one surface is a circuit-forming surface and the other surface is a non-circuit-forming surface. The wafer to which the present invention can be applied is usually a semiconductor wafer. Examples of the semiconductor wafer include not only silicon wafers but also gallium nitride wafers, lithium tantalate wafers, lithium niobate wafers, silicon carbide wafers, germanium wafers, gallium arsenide wafers, gallium phosphide wafers, and gallium arsenide aluminum wafers. The thickness of the wafer is not particularly limited, but is preferably 600 to 800 μm, more preferably 625 to 775 μm. For example, a transparent substrate that transmits light is used as the support.
[0088] [Step (b)] Step (b) is a step of photocuring the adhesive. After the wafer processed body (laminate substrate) is formed, the adhesive is photocured with visible light or ultraviolet light (whose wavelength or center wavelength is preferably 350 to 405 nm, more preferably 365 to 405 nm, and most preferably 385 to 405 nm) with an energy amount of 1 to 20,000 mJ / cm2. 2 It is preferable to irradiate so that the energy amount is 1 mJ / cm 2 Above this level, sufficient adhesion is obtained, and 20,000 mJ / cm 2 If the energy is less than this, the productivity is excellent, decomposition products from the photoradical polymerization initiator are unlikely to be generated, and outgassing is also suppressed. In terms of productivity, adhesion, low outgassing, and easy peeling, the energy is 1000 to 10000 mJ / cm 2 is more preferred.
[0089] When curing the composition, black light, UV-LED, or visible light-LED can be used as a light source, and for example, the following light sources can be used. As black light, a light containing a component with a wavelength of 385 nm or more is preferably used, regardless of its central wavelength. In addition, when a wavelength range is described in this specification, whether or not the central wavelength is included in the range is used to determine whether or not the range is included. Black light (center wavelength 365 nm, illuminance 10 mW / cm 2 , Toyo Adtec Co., Ltd. TUV-8271) ·UV-LED (wavelength 385±5nm, illuminance 350mW / cm 2 (Conditions: Working distance from the tip of the mirror unit is 20mm, HOYA Corporation H-4MLH200-V2-1S19 + specially designed mirror unit) ·UV-LED (wavelength 395±5nm, illuminance 375mW / cm 2 (Conditions: Working distance from the tip of the mirror unit is 20mm, HOYA Corporation H-4MLH200-V3-1S19 + specially designed mirror unit) ·UV-LED (wavelength 405±5nm, illuminance 400mW / cm 2 (Conditions: Working distance from the tip of the mirror unit is 20mm, HOYA Corporation H-4MLH200-V4-1S19 + specially designed mirror unit) ·UV-LED (center wavelength 405nm, illuminance 10mW / cm 2 , CCS HLDL-120V0-NWPSC) ·Visible light-LED (wavelength 451±5nm, illuminance 550mW / cm 2 (Condition: Work distance from the tip of the irradiation unit is 10 mm, HLDL-155VL450‐PSC manufactured by CCS Corporation) ·Visible light-LED (wavelength 492±5nm, illuminance 400mW / cm 2 (Condition: Work distance from the tip of the irradiation unit is 10 mm, HLDL-155BG-PSC manufactured by CCS Corporation)
[0090] In a preferred embodiment, the light source may be a UV-LED or a visible light-LED, which requires a smaller integrated amount of light (shorter irradiation time) than a black light, which generally has a broad irradiation wavelength and therefore requires a larger integrated amount of light and a longer irradiation time. In other words, by using an LED light source with a narrow irradiation wavelength band, temporary fixing can be performed in a short time, and as a result, the time required for the manufacturing process can be shortened.
[0091] [Process (c)] Step (c) is a step of grinding and / or polishing the non-circuit-forming surface of the wafer bonded to the support, i.e., a step of grinding the back side of the wafer of the wafer processed body obtained by bonding in step (a) to reduce the thickness of the wafer. The thickness of the thinned wafer is preferably 10 to 300 μm, more preferably 30 to 100 μm. There is no particular restriction on the method of grinding / polishing the back side of the wafer, and a known grinding / polishing method is adopted. Grinding is preferably performed while cooling by pouring water on the wafer and grindstone (such as a diamond-edged grindstone).
[0092] [Step (d)] Step (d) is a step of processing the non-circuit-forming surface of the wafer processed body with the non-circuit-forming surface ground / polished, i.e., the wafer processed body thinned by back grinding / polishing. This step includes various processes used at the wafer level. For example, electrode formation, metal wiring formation, protective film formation, etc. More specifically, conventionally known processes include metal sputtering for forming electrodes, etc., wet etching for etching the metal sputtering layer, application of resist as a mask for metal wiring formation, exposure, and development to form a pattern, resist peeling, dry etching, formation of metal plating, silicon etching for TSV formation, and oxide film formation on the silicon surface.
[0093] [Step (e)] Step (e) is a peeling step. This step is a step of peeling off the wafer processed in step (d) from the wafer processed body. For example, after various processing is performed on the thinned wafer, the wafer is peeled off from the wafer processed body before dicing. At this time, a dicing tape can be attached to the thinned and processed surface in advance. This peeling step is generally performed under relatively low temperature conditions, from room temperature to about 60°C. As this peeling step, any of the well-known UV laser peeling step, IR laser peeling step, and mechanical peeling step can be adopted.
[0094] The UV laser peeling process is, for example, a process in which a UV laser is irradiated onto the entire surface of the wafer processed body so as to scan linearly back and forth in a tangential direction from the end of the optically transparent support side of the wafer processed body, and the adhesive layer is decomposed by the energy of the laser to peel it off. Such a peeling process is described, for example, in JP-T-2019-501790 and JP-T-2016-500918.
[0095] The IR laser peeling step is, for example, a step of irradiating the entire surface of the wafer processed body with an IR laser so as to scan linearly back and forth in a tangential direction from the end of the optically transparent support side of the wafer processed body, and heating and decomposing the adhesive layer by the energy of the laser to peel it off. Such a peeling step is described, for example, in Japanese Patent No. 4565804. In order to carry out this IR laser peeling step, a light-to-heat conversion layer (for example, 3M's LTHC; Light-To-Heat-Conversion release coating) that absorbs IR laser light and converts it to heat may be provided between the temporary fixing agent layer and the glass support. When using 3M's LTHC, for example, LTHC is spin-coated on the glass support and cured. Then, the temporary fixing agent layer can be spin-coated on the wafer, and then bonded to the glass support on which the LTHC layer is formed, and UV-cured. A method of carrying out the IR laser peeling step using 3M's LTHC is described, for example, in the same Japanese Patent No. 4565804 as above.
[0096] The mechanical peeling process is, for example, a peeling process including a process in which a blade is inserted into the interface end of a wafer processed body to generate a cleavage between the wafer and the support, the wafer of the wafer processed body is fixed horizontally with the wafer facing down, and after the blade is inserted, an upward stress is applied to the upper support and / or the blade to develop the cleavage and peel off the wafer and the support. Such a peeling process is described, for example, in Japanese Patent No. 6377956 and Japanese Patent Laid-Open No. 2016-106404.
[0097] Any of these peeling methods can be used to peel off the composition. At this time, it is preferable to fix one of the wafer or support of the wafer processed body horizontally, insert a blade or use a solvent (e.g., an aliphatic or aromatic hydrocarbon solvent such as pentane, hexane, heptane, octane, nonane, decane, benzene, toluene, xylene, mesitylene, etc.) to swell the outer periphery of the adhesive layer to trigger peeling, and then lift the other side at a certain angle from the horizontal direction. These peeling methods are usually performed at room temperature, but it is also preferable to heat the material to a maximum of about 90°C. When using a laser, it is preferable to use a YAG laser or a YVO4 laser.
[0098] The step of peeling the processed wafer from the support in the above step (e) further includes, in the case of a mechanical peeling step, (f) adhering a dicing tape to the wafer surface of the processed wafer; (g) vacuum-adsorbing the dicing tape surface onto the adsorption surface; (h) peeling the support from the processed wafer while the temperature of the adsorption surface is in the range of 10 to 100° C.; In this way, the support can be easily peeled off from the processed wafer, and the subsequent dicing step can be easily carried out.
[0099] In addition, in the case of peeling with a UV laser or an IR laser, the manufacturing method further includes, for example: (i) placing / fixing the processed wafer, optically transparent support side up, on a horizontal surface, preferably via a dicing tape; (j) irradiating the entire surface of the processed wafer with a laser from the support side of the wafer in a scanning manner; In this way, the support can be easily peeled off from the processed wafer, and the subsequent dicing step can be easily carried out.
[0100] In addition, after the step of peeling the processed wafer from the support by a UV laser or an IR laser in step (e), (k) removing the temporary fixing agent remaining on the surface of the wafer; It is necessary to carry out the above. Methods for removing the temporary fixing agent include a method in which, while the thinned surface is vacuum-adsorbed onto the adsorption surface, an adhesive tape such as a dicing tape is applied to the entire surface of the other surface on which the temporary fixing agent remains, and the temporary fixing agent is peeled off together with the tape, and a method in which the wafer is immersed in a solvent (e.g., an aliphatic or aromatic hydrocarbon solvent such as pentane, hexane, heptane, octane, nonane, decane, benzene, toluene, xylene, mesitylene, etc.) to swell the adhesive layer and peel it off. Of these methods, the tape peeling method is preferred in terms of the small number of steps and the short time required.
[0101] After the temporary fixing agent is removed, the wafer can be directly subjected to the next process without cleaning the surface. (l) A process of cleaning the wafer from which the support and temporary fixing agent have been removed, with the circuit-forming surface facing up, using a solvent (e.g., an aliphatic or aromatic hydrocarbon solvent such as pentane, hexane, heptane, octane, nonane, decane, benzene, toluene, xylene, or mesitylene). It is preferable to carry out the following.
[0102] In the step (k), the adhesive (temporary fixing agent) may remain partially on the circuit formation surface of the wafer from which the temporary fixing agent has been removed. In addition, it is preferable to wash and reuse the peeled support, but adhesive residues may also be attached to the surface of the support. Methods for removing these adhesive residues include a method of immersing the support in a solvent (e.g., an aliphatic or aromatic hydrocarbon solvent such as pentane, hexane, heptane, octane, nonane, decane, benzene, toluene, xylene, or mesitylene) and swelling the support to peel it off.
[0103] In one embodiment, various techniques such as those described below can be used to cure the composition to obtain a cured product.
[0104] As a first method, a layer made of a temporary fixing composition containing the above-mentioned components can be cured to obtain a single-layer cured body.
[0105] The second method is to prepare a first layer made of a temporary fixing composition containing at least the (A) and (B) components but not the (D) component UV absorber, and a second layer made of a temporary fixing composition containing at least the (A), (B), and (D) components, and then cure the first layer to obtain a cured body having an integrated single layer or multiple layers (composite layers). In this cured body, it is preferable that the concentration distribution of the components is different in the thickness direction, or that the concentration distribution of the components is different on the upper and lower surfaces in the thickness direction of the cured body. The difference in the concentration distribution of the components can be confirmed by quantifying the UV transmittance on both sides of the cured body using the reflectance measurement spectroscopy described above. This method provides the effect of combining layers with different light transmittances to realize optimal curing. In addition, a black light or a UV-LED can be used as a light source for the above-mentioned curing (the same applies to the method described below). An example of a black light is TUV-8271 (center wavelength 365 nm, illuminance 10 mW / cm) manufactured by Toyo Adtec Co., Ltd. 2) as UV-LED. HOYA Corporation's H-4MLH200-V2-1S19 + specially designed mirror unit (wavelength 385±5nm, illuminance 350mW / cm 2 ,Conditions: Scan pitch from the tip of the mirror unit 20 mm), HOYA Corporation H-4MLH200-V3-1S19 + specially designed mirror unit (wavelength 395 ± 5 nm, illuminance 375 mW / cm 2 ,Conditions: Working distance from the tip of the mirror unit 20 mm), HOYA Corporation H-4MLH200-V4-1S19 + specially designed mirror unit (wavelength 405 ± 5 nm, illuminance 400 mW / cm 2 , Conditions: Working distance from the tip of the mirror unit is 20 mm.
[0106] As a third method, a cured body having an at least partially integrated single layer can be obtained by applying (e.g., applying by spin coating) component (D) onto a cured layer made of a temporary fixing composition containing at least components (A) and (B). In this case, the concentration distribution of the components varies in the thickness direction of the cured body. The concentration distribution of the components can be quantified by reflectance measurement spectroscopy for each target layer as described above. This method has the effect of precisely controlling the UV absorption characteristics.
[0107] As a fourth method, a layer of a commercially available LTHC agent (light-to-heat conversion agent) may be placed on a layer of a temporary fixing composition containing at least the (A) component and the (B) component, and cured to obtain a multi-layer cured body. This has the effect of easily obtaining a cured body.
[0108] The cured product obtained by the above-mentioned method can be combined with an adherend to provide a structure.
[0109] There are various examples of the method for producing the structure as described above. For example, the first production method may include a step of applying a first temporary fixing composition containing at least the (A) component and the (B) component but not the (D) component on a wafer and partially curing the composition, a step of applying a second temporary fixing composition containing at least the (A), (B), and (D) components on the partially cured temporary fixing composition, and a step of further placing a transparent substrate on the applied second temporary fixing composition and photocuring the composition.
[0110] In addition, a second manufacturing method of the structure may include a step of applying a first temporary fixing composition containing at least the (A) component and the (B) component but not the (D) component onto a wafer and partially curing it as necessary, a step of applying a second temporary fixing composition containing at least the (A), (B), and (D) components onto a transparent substrate and partially curing it as necessary, and a step of bringing the surfaces of the wafer and the transparent substrate onto which the temporary fixing compositions are applied into close contact with each other, and then bonding them by photocuring.
[0111] Furthermore, a third manufacturing method for the structure may include the steps of applying a temporary fixing composition containing at least the (A) component and the (B) component but not the (D) component onto a wafer and partially curing it as necessary, applying an LTHC layer onto a transparent substrate, drying and curing it, and bringing the surface of the wafer on which the temporary fixing composition has been applied into close contact with the surface of the transparent substrate on which the LTHC layer has been applied, and then bonding them by photocuring.
[0112] In addition to the above-mentioned temporary fixing composition, the same composition used in the temporary fixing composition of the present invention can also be used as a raw material for the light-to-heat conversion (LTHC) layer that absorbs IR laser light and converts it into heat, as described in Japanese Patent No. 4565804. By adding this composition as a component of the light-to-heat conversion (LTHC) layer, it is possible to improve its heat resistance.
[0113] In one embodiment, a method for producing a semiconductor wafer can be provided, which includes the steps of applying a temporary fixing composition to a semiconductor wafer substrate and / or a support member to bond the semiconductor wafer substrate and the support member, curing the temporary fixing adhesive by irradiating light having a wavelength of 350 to 700 nm (preferably 365 to 500 nm, more preferably 385 to 450 nm) to obtain an adhesive body, and irradiating the adhesive body with laser light having a wavelength of less than 385 nm (preferably laser light having a wavelength of 200 nm or more and less than 385 nm) to peel off the semiconductor wafer substrate. This production method has the advantages that the curing and peeling steps are both performed at room temperature, there is no need to heat or cool the member, there is generally no need to use a solvent, and the method is simple and has a short cycle time.
[0114] Furthermore, the cured temporary fixing adhesive may form a single layer in the adhesive body, which makes it possible to simplify the process and shorten the tact time.
[0115] In a preferred embodiment, the composition contains both the photoradical polymerization initiator (B) and the UV absorber (D), which are preferred above, and thus even if the temporary fixing adhesive is a single layer, it is possible to achieve both a fast curing rate and a fast peeling rate. Furthermore, when the temporary fixing adhesive is UV-cured, it is possible to significantly reduce the amount of uncured UV-curable monomer components remaining in the cured body, thereby improving the heat resistance of the cured body and reducing the volatile content under a nitrogen atmosphere. That is, for example, it is possible to increase the 2% heat mass loss temperature in the Tg / DTA measurement of the cured body. A temporary fixing adhesive having high heat resistance of the cured body and reduced volatile content under a nitrogen atmosphere is extremely useful for recent semiconductor manufacturing processes. The cured body may preferably have a 2% mass loss temperature of 300°C or higher, preferably 320°C or higher, more preferably 326°C or higher under a nitrogen atmosphere. EXAMPLES
[0116] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to these.
[0117] Unless otherwise specified, the experiments were performed at 23°C and 50% humidity. Curable resin compositions (hereinafter sometimes referred to as liquid resin compositions) having the compositions (units: parts by mass) shown in the table below were prepared and evaluated. The following compounds were selected as each component.
[0118] [Table 1]
[0119] [Table 2]
[0120] [Table 3]
[0121] (composition) The following was used as component (A-1). A-BPEF-2: 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate ("NK Ester A-BPEF-2" manufactured by Shin-Nakamura Chemical Co., Ltd.) A-BPE-2: Ethoxylated bisphenol A diacrylate ("NK Ester A-BPE-2" manufactured by Shin-Nakamura Chemical Co., Ltd., in the structural formula below, R = -CH2CH2O-, m = n = 1) A-BPP-3: Ethoxylated bisphenol A diacrylate ("NK Ester A-BPP-3" manufactured by Shin-Nakamura Chemical Co., Ltd., in the following structural formula, R = -CH2CH(CH3)-, m + n ≒ 3) ABE-300: Ethoxylated bisphenol A diacrylate ("NK Ester ABE-300" manufactured by Shin-Nakamura Chemical Co., Ltd., in the following structural formula, R = -CH2CH2O-, m + n ≒ 3)
[0122] [ka]
[0123] The following was used as component (A-2). HBPE-4: EO modified hydrogenated bisphenol A diacrylate ("HBPE-4" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., m+n≒4) A-DCP: Tricyclodecane dimethanol diacrylate ("NK Ester A-DCP" manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0124] The following was used as component (B): Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BASF "Irgacure 819")
[0125] The following was used as component (C): HX-620: Caprolactone-modified hydroxypivalic acid neopentyl glycol diacrylate ("Kayarad HX-620" manufactured by Nippon Kayaku Co., Ltd., m+n≒4) HX-220: Caprolactone-modified hydroxypivalic acid neopentyl glycol diacrylate ("Kayarad HX-220" manufactured by Nippon Kayaku Co., Ltd., m+n≒2) PHOTOMER-4362: Hexanediol [2PO] diacrylate (IGM "PHOTOMER 4362") DDDA: 1,10-decanediol diacrylate (Hitachi Chemical Co., Ltd. "FA-1210A") NDDA: 1,9-nonanediol diacrylate ("Viscoat #260" manufactured by Osaka Organic Chemical Industry Co., Ltd.) RC100C: An acrylate polymer having acryloyl groups at both ends (Kaneka XMAP RC100C, manufactured by Kaneka Corporation, having the following structural formula)
[0126] [ka]
[0127] The following was used as component (D): 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine (BASF "Tinuvin 460")
[0128] The following was used as component (E): DTDA: 2-decyl-1-tetradecanyl acrylate (Kyoeisha Chemical Co., Ltd. "Light Acrylate DTD-A") nSTA: n-Stearyl acrylate ("STA" manufactured by Osaka Organic Chemical Industry Co., Ltd.) ISTA: Isostearyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., "ISTA")
[0129] The following was used as component (F): RA-341: Trifunctional or higher multifunctional methacrylate polymer ("ART CURE RA-341" manufactured by Negami Chemical Industries, Ltd., weight average molecular weight 80,000)
[0130] (Preparation of liquid samples) The materials were heated and mixed at 80°C to form a uniform mixture. Any examples in which precipitation occurred at this stage were excluded from the following evaluations. Additionally, as described below, any examples in which curing was insufficient and any examples that melted at 300°C or less when heated were also excluded from the evaluations.
[0131] (Measurement of storage modulus) The liquid resin composition homogenized by the above-mentioned warm mixing was sandwiched between PET films and spread to a thickness of 50 μm, and the accumulated light dose was 5000 mJ / cm 2 The curing was performed under the above conditions to prepare a cured sample. A UV-LED (center wavelength 405 nm, illuminance 100 mW / cm2) was used for curing. 2 A HTLC-120V0-NWPSC (manufactured by CCS) was used.
[0132] The dynamic viscoelasticity of the cured samples was measured using a viscoelasticity measuring device RSA-G2 manufactured by TA Instruments Japan Co., Ltd. Measurements were performed with a chuck distance of 7 mm, sample width of 5 mm, sample thickness of 50 μm, strain of 0.1%, tensile frequency of 1 Hz, heating rate of 3°C / min, and temperature range of -50°C to 250°C, and the value of E' at 23°C was calculated.
[0133] (Measurement of 2% mass loss temperature) The liquid resin composition homogenized by the above-mentioned warm mixing was sandwiched between PET films and spread to a thickness of 50 μm, and the accumulated light dose was 5000 mJ / cm 2 The curing was performed under the above conditions to prepare a cured sample. A UV-LED (center wavelength 405 nm, illuminance 100 mW / cm2) was used for curing. 2 A HTLC-120V0-NWPSC (manufactured by CCS) was used.
[0134] The weighed 10 mg sample of the cured body was heated from room temperature to 600°C at a heating rate of 10°C / min under a nitrogen flow with a carrier gas flow rate of 70 ml / min using a Netsch Japan Co., Ltd. STA-2500 differential thermal and thermogravimetric simultaneous measurement device, and then the cured body was weighed. From this, the thermal mass loss rate (2% mass loss temperature) in a nitrogen atmosphere was calculated.
[0135] (Evaluation of vacuum heat resistance) A 4-inch sample was prepared by bonding a 4-inch silicon wafer (diameter 10 cm x thickness 50 μmt) and a 4-inch glass wafer (diameter 10 cm x thickness 0.7 mm) together using the prepared liquid resin composition. Similarly, an 8-inch sample was prepared by bonding an 8-inch silicon wafer (diameter 10 cm x thickness 50 μmt) and an 8-inch glass wafer (diameter 20 cm x thickness 70 μmt) together using the liquid resin composition. When bonding, the thickness of the resin composition was adjusted by adding 0.1 mass% of silica particles (trade name Hi-Presica TS N3N, average particle size 50 μm) manufactured by Ube Exsymo Co., Ltd. to the temporary fixing agent and mixing it. After bonding, the LED integrated light quantity was 5000 mJ / cm. 2 (Center wavelength 405nm, illuminance 100mW / cm 2) to prepare a bonded sample. 2 A HTLC-120V0-NWPSC (manufactured by CCS) was used.
[0136] Each bonded sample was placed in a vacuum hot plate chamber and heated at 300°C and 20 Pa for 1 hour, after which the circumferential edge of the bonded sample was visually observed and evaluated according to the following criteria. The evaluation result of the 4-inch sample is shown in the table as "Vacuum heat resistance 4in50μmt." The evaluation result of the 8-inch sample is shown in the table as "Vacuum heat resistance 8in70μmt." Excellent: The edges were not peeled off at all. Good: The length of the peeled portion at the end was less than 5 mm from the edge. Passable: The length of the peeled end was 5mm or more but less than 10mm from the edge. Unacceptable: The length of the peeled off edge was 10 mm or more from the edge.
[0137] (Evaluation of tape peelability) A peeling tape (Denka's "ELEGRIP (registered trademark) TAPE P-Series") was attached to the above-mentioned bonded sample to prepare a peeling sample. A biaxial tensile test system (Shimadzu's "Autograph AG-Xplus") was used to perform a peeling test under the following conditions. Peeling direction: 90° Peeling speed: 2mm / sec Measurement width: 25mm Stroke: 80mm Test thickness: 0.070mm Presser bar: φ7mm Pressure: 1N / mm 2
[0138] It was visually confirmed whether or not the tape cracked when peeled off.
[0139] From the above results, the compositions according to the examples of the present invention were excellent in both heat resistance and tape peelability. On the other hand, Comparative Examples 1 to 4, 7, 8, and 12 to 16, which did not satisfy the storage modulus conditions, all had problems with tape peelability. In addition, Comparative Examples 9 to 11, which did not contain component (A), all had poor prognosis. Comparative Example 5, which had a storage modulus of more than 0.66 GPa, had problems with heat resistance. Comparative Example 6 did not have a substantial storage modulus due to precipitation during production, and also did not satisfy the conditions of the present invention.
[0140] An experiment was carried out to grind the non-circuit-formed surface (rear surface) of a silicon wafer processed body obtained by bonding a silicon wafer to a glass support using the compositions of Examples 3 and 4 (i.e., reproduction of the above-mentioned step (c)). The thickness of the glass support before processing was about 715 μm, and the thickness of the silicon wafer was about 722 μm. The thickness was calculated as the average value of five trial results.
[0141] Thickness of silicon wafer processed body using the composition of Example 3 as a temporary fixing adhesive layer Before back grinding: 1506.6μm After back grinding: 833.8μm Silicon wafer thickness after grinding: 49.7μm
[0142] Thickness of silicon wafer processed body using the composition of Example 4 as a temporary fixing adhesive layer Before back grinding: 1508.8μm After back grinding: 835.0μm Silicon wafer thickness after grinding: 49.8μm
[0143] From the above experimental results, it was confirmed that in the case of a silicon wafer processed body in which the composition according to the embodiment of the present application was used as a temporary fixing adhesive, the silicon wafer could be suitably thinned.
Claims
1. A temporary fixing composition comprising the following components (A) to (B) and (E) as an optional additional component, the composition having a storage modulus of elasticity at 23° C. of 0.66 GPa or less after curing: (A) Bifunctional (meth)acrylate having a cyclic skeleton (B) Photoradical polymerization initiator (E) Monofunctional (meth)acrylate Here, component (A) is (A-1) an aromatic difunctional (meth)acrylate, and (A-2) Alicyclic bifunctional (meth)acrylate Includes. The cured body was prepared by sandwiching the temporary fixing composition between PET films, spreading it to a thickness of 50 μm, and applying UV-LED (center wavelength 405 nm, illuminance 100 mW / cm 2 ) with an integrated light dose of 5000 mJ / cm 2 The composition was cured under the following conditions. When component (E) is present, the mass ratio of component (E) to component (A) is more than 0% and not more than 50%.
2. The temporary fixing composition according to claim 1, characterized in that at least one of the components (A-1) and (A-2) has a fused ring skeleton.
3. The temporary fixing composition according to claim 1 or 2, further comprising the following (C): (C) Acyclic aliphatic bifunctional (meth)acrylate
4. The temporary fixing composition according to claim 3 , wherein the component (C) includes an oligomer and / or a polymer.
5. The temporary fixing composition according to claim 3 , wherein the amount of the component (A) is 50% or more in the mass ratio of the component (A) to the component (C).
6. The temporary fixing composition according to claim 1 or 2, further comprising the following (D): (D) UV absorber
7. The temporary fixing composition according to claim 1 or 2, further comprising the following (F): (F) Trifunctional or higher polyfunctional (meth)acrylate
8. The temporary fixing composition according to claim 7 , wherein the mass ratio of the component (A) to the component (F) is more than 0% and 50% or less.
9. A cured product of the temporary fixing composition according to claim 1 or 2.
10. The hardened body according to claim 9, which has a 2% mass loss temperature of 300° C. or higher in a nitrogen atmosphere.
Citation Information
Patent Citations
(METH) acrylic resin composition and adhesion / dismantlement method
JP2014091774A
Photocurable composition
WO2015056632A1
Photoradically polymerizable composition
WO2021172341A1
Composition
WO2021235406A1